The Impact of Fuel Prices Increasing on Inflation in South Sulawesi using Pulse Function Intervention Analysis - Desy Wasani; Nucke Widowati Kusumo Projo (Jurnal Ekonomi Pembangunan, 2022)
South Sulawesi Province is considered capable of controlling inflation, as seen from its not very large volatility. However, this does not mean that the increase in fuel prices does not impact inflation in South Sulawesi. This study aims to obtain the best model to analyze the impact of rising fuel prices on inflation in South Sulawesi using Pulse Function Intervention Analysis and to find out how significant the impact of rising fuel prices on inflation in South Sulawesi is. The data in this study were obtained from the Central Statistics Agency (BPS) of South Sulawesi Province, namely the monthly inflation of South Sulawesi Province for the period January 2014 – September 2022, with a total of 105 observations. The best model in this study is the MA ([12]) bbm1, bbm5, and bbm6 models with AIC 104.09. Statistical test results show that 3 of 6 times increases in fuel prices since 2014 still influence the rising inflation, namely in November 2014, April 2022, and September 2022. The increase in fuel prices in 2014 impacted rising inflation by 1.97 percent, while in 2022, it increased inflation by 0.92 and 0.99 percent.